2015
DOI: 10.1177/1545968314567150
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Highly Challenging Balance Training in Elderly With Parkinson’s Disease

Abstract: Background. Highly challenging exercises have been suggested to induce neuroplasticity in individuals with Parkinson’s disease (PD); however, its effect on clinical outcomes remains largely unknown. Objective. To evaluate the short-term effects of the HiBalance program, a highly challenging balance-training regimen that incorporates both dual-tasking and PD-specific balance components, compared with usual care in elderly with mild to moderate PD. Methods. Participants with PD (n = 100) were randomized, either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
280
2
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 188 publications
(309 citation statements)
references
References 58 publications
13
280
2
14
Order By: Relevance
“…The eligibility criteria were similar to that used in the RCT (Conradsson et al., 2015) however, the recruitment process revealed that younger patients (<60 years) are commonly referred to rehabilitation in primary healthcare settings. To promote access, the implementation trial will include persons of all ages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The eligibility criteria were similar to that used in the RCT (Conradsson et al., 2015) however, the recruitment process revealed that younger patients (<60 years) are commonly referred to rehabilitation in primary healthcare settings. To promote access, the implementation trial will include persons of all ages.…”
Section: Discussionmentioning
confidence: 99%
“…Similar positive trends were found for secondary outcomes, that is, gait speed, concerns of falling, and exercise endurance. In fact, a similar (average) difference in gait speed was found following training in the Group 2x + HEP when compared to the efficacy trial (Conradsson et al., 2015). The fact that the findings of the two studies corroborate are an indication of the potential effectiveness of the adapted training dose in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They expressed imbalance in Parkinson's disease as occurs by combination of many disorders including loss of postural reflexes, insufficiency in postural adjustments, rigidity in the trunk and extremities and akinesia. Introducing balance training program to their PD patients provide great benefits to gait stability [21]. The optimum time for TMS intervention after PD remains unclear, so, we recruited patients 12-18 months after their ictus.…”
Section: Transcranial Magnetic Stimulation Versus Electrical Vestibulmentioning
confidence: 99%
“…Considering the higher rate of imbalance and falls in old patients with PD rather than healthy ones, this type of exercises can therefore play a key role in improving motor functions and balance in these patients [14]. Conradsson et al (2015) reported significantly higher effects on neural adaptations in patients with PD for advanced balance exercises compared to conventional therapeutic methods [15]. Canning et al…”
Section: Introductionmentioning
confidence: 99%